2001
DOI: 10.4314/sajas.v31i3.3796
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic relationships between lamb and ewe traits for the Sabi sheep of Zimbabwe

Abstract: Genetic and phenotypic correlations were estimated between lamb and ewe traits in a flock of Sabi sheep reared at the Matopos Research Station. Direct additive estimates of heritability were: 0.28 ± 0.04; 0.17 ± 0.00; 0.25 ± 0.01; 0.39 ± 0.01; 0.59 ± 0.01; 0.50 ± 0.01; 0.68 ± 0.03; 0.12 ± 0.003; 0.25 ± 0.01; 0.11 ± 0.00; 0.12 ± 0.00; for birth weight, weaning weight (120 days), 12 month weight, 18 month weight, ewe mating weight, post partum weight, ewe weight at weaning of lamb, total weight of lamb weaned, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
14
1
1
Order By: Relevance
“…8, 12.69±2.38, 20.72±4.33, 21.65±5.53 and 14.53±3.20 kg at weaning, in Zimbabwe Sabi lambs (Matika et al 2001), in Egyptian Farafra lambs (Mousa et al 2006), in Iranian Zandi lambs (Ghafouri-Kesbi & Eskandarinasab 2008), in Arman lambs (Farokhad et al 2011) and in Indian Malpura lambs (Gowane et al 2015), respectively. Ghafouri-Kesbi (2013) reported that statistics of Kleiber Ratio at pre-weaning period were 19.61±2.4 (CV= 12.2%) in fat-tailed Mehraban lambs.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 12.69±2.38, 20.72±4.33, 21.65±5.53 and 14.53±3.20 kg at weaning, in Zimbabwe Sabi lambs (Matika et al 2001), in Egyptian Farafra lambs (Mousa et al 2006), in Iranian Zandi lambs (Ghafouri-Kesbi & Eskandarinasab 2008), in Arman lambs (Farokhad et al 2011) and in Indian Malpura lambs (Gowane et al 2015), respectively. Ghafouri-Kesbi (2013) reported that statistics of Kleiber Ratio at pre-weaning period were 19.61±2.4 (CV= 12.2%) in fat-tailed Mehraban lambs.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Direct estimates of heritability in sheep breeds for LBW were 0.28±0.04 in Sabi (Matika et al 2001), 0.06 in Swedish finewool (Näsholm & Danell 1996), 0.13 in Suffolk (Yamaki 1994), 0.14-0.20 in Baluchi (Yazdi et al 1997), 0.43 in Segurena (Analla et al 1997) and 0.15±0.05 in Romney (Ibrahim 2015). Furthermore, estimates for LWW were 0.17±0.00 in Sabi (Matika et al 2001), 0.34 in Suffolk (Yamaki, 1994, 0.15 Swedish finewool (Näsholm & Danell 1996), 0.13-0.19 Baluchi (Yazdi et al 1997, 0.31 Segurena (Analla et al 1997) and 0.08±0.03 in Romney (Ibrahim 2015).…”
Section: Variance Componentsmentioning
confidence: 99%
“…The ranges of both the heritability index (0.01-0.39) and repeatability index (0.090-0.670) of fertility as seen in earlier works have been large: Lee, et all, 2009, Matika, et al, 2001, Matos et al, 1997, Olesen, et al, 1994,Olivier, et al, 1998, Piwczyński, et al, 2004, Piwczyński and Mroczkowski, 2009, Rosati, et al, 2002, Sousa, et all, 2000, Vatankhah, et al, 2006. One may assume that, similarly as in the authors' own research, this is largely due to which method and the model of statistical analysis was used (Matos et al, 1997, Olesen, et al, 1994, Piwczyński and Mroczkowski, 2009, Sousa, et all, 2000, Vatankhah, et al, 2006.…”
Section: Discussionmentioning
confidence: 79%
“…Unfortunately, genetic improvement in this area is very difficult relative to other production traits characterized with lower genetic conditioning (Matika, et al, 2001, Matos et al, 1997, Piwczyński, et al, 2004, Piwczyński and Mroczkowski, 2009, Sousa, et all, 2000. Moreover, discovering the genetic conditioning of fertility is more complicated than in the case of, for instance, body weight or milk yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation